Characterization of the circadian typology in university students in relation to the type of career - Arlan Machado Rojas; Yunier Broche Pérez; Osvaldo Norman Montenegro; María Elena de la Torre Santos; Daniel Tirado Saura; Carolina Machado de la Torre (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2019)
Foundation: Chronotype is an attribute of human beings, which reflects its individual circadian phase, and affects biological and psychological functions, both in health and disease. Its study is particularly valuable in educational settings. Objective: to characterize the chronotype of university students in relation to the type of career they study. Methods: a cross-sectional analytical study was conducted in a series of 273 university students, selected by simple random sampling, structured in three groups based on provenance criteria: 88 from Technical Sciences, 88 from Social and Humanistic Sciences and 97 from Medical Sciences. The chronotype of each subject was explored through the Morningness and Eveningness Questionnaire. For each group the mean scores of the questionnaire and the proportions of morning, intermediate and evening individuals were calculated. Results: the mean scores of the three groups were framed in the intermediate chronotype range, and there were no statistically significant differences. Subjects were classified as 67% of as intermediate, 23.8% as morning and 9.2 % as evening; chronotype proportions by groups also showed no significant differences. Conclusion: there was a clear predominance of intermediate chronotype, followed in frequency by morning and evening. It was not demonstrated that the type of career influenced scores, nor in proportions of the circadian typologies by groups.